Cardiovascular Sound and the Stethoscope, 1816 to 2016: The Twenty-Fifth Louis Gross Memorial Lecture - Segall, Harold N. (1963)
Cardiovascular sound escaped attention until Laennec invented and demonstrated the usefulness of the stethoscope. Accuracy of diagnosis using cardiovascular sounds as clues increased with improvement in knowledge of the physiology of circulation. Nearly all currently acceptable clinicopathological correlations were established by physicians who used the simplest of stethoscopes or listened with the bare ear. Certain refinements followed the use of modern methods which afford greater precision in timing cardiovascular sounds. These methods contribute to educating the human ear, so that those advantages may be applied which accrue from auscultation, plus the method of writing quantitative symbols to describe what is heard, by focusing the sense of hearing on each segment of the cardiac cycle in turn. By the year 2016, electronic systems of collecting and analyzing data about the cardiovascular system may render the stethoscope obsolete.